Electromagnetically-induced change in interfacial tension and contact angle of oil droplet using dielectric nanofluids. (1st January 2020) - Adil, Muhammad; Mohd Zaid, Hasnah; Kean Chuan, Lee
Abstract: Nanoparticles have been studied as promising agents to reduce interfacial tension (IFT) and contact angle, which are two main mechanisms for enhanced oil recovery (EOR). Despite their advantages, the nanoparticles tend to agglomerate due to the drastic conditions of the reservoir, i.e., high temperature and/or high concentration of electrolytes, which lead to their separation from the oil/water interface and subsequent retention in a porous medium. Dielectric nanoparticles, as a suitable replacement for environmentally sensitive chemical EOR, had been proposed due to their thermal properties including high melting point. But more notably, these nanoparticles, coupled with low frequency electromagnetic (EM) waves, can be polarized to create disturbances at the oil/nanofluid interface, such that oil can be released from the reservoir rock surfaces and easily moved to the production well. However, the knowledge of nanoparticles' characteristics (including morphology and dielectric properties) corresponding to different calcination temperatures that influence the recovery mechanism is still insufficient. For this purpose, dielectric nanofluids were prepared in brine with SDBS as a dispersant, using as-synthesized zinc- (ZnO) and aluminum-oxide (Al2 O3 ) with an average crystallite size of 43.4–47.3 nm and 25–94.3 nm, respectively. Upon the measurement of the IFT of the crude oil/nanofluids system, it was shown that the rotational polarization, which depends on the dielectric loss of nanoparticles, was the major contributor to the enhanced interfacial disturbance through oil droplet deformation. These results have revealed a potential way to improve the oil displacement mechanism by employing the dielectric nanofluids under an EM field.